1981
DOI: 10.1111/j.1399-3054.1981.tb06043.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Mg2+ and Ca2+, and Mg2+‐stimulated adenosine triphosphatase activity in oat roots as affected by mineral nutrition

Abstract: Mg2+‐ and Ca2+‐uptake was measured in dark‐grown oat seedlings (Avena sativa L. cv. Brighton) cultivated at two levels of mineral nutrition. In addition the stimulation of the ATPase activity of the microsomal fraction of the roots by Mg2+ was measured. Ca2+‐uptake by the roots was mainly passive. Mg2+‐uptake mainly active; the passive component of Mg2+‐uptake was accompanied by Ca2+‐efflux up to 60% of the Ca2+ present in the roots. In general Mg2+ ‐uptake of oat roots was biphasic. The affinity of the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Several lines of evidence indicate that ATPases are implicated in active ion uptake (Hodges 1976, Stok et al 1981. In accordance with the mechanism proposed here, an ATPase reaction could be associated to each reaction leading from a P, form to the following Pj+, form of the carrier.…”
Section: Furtber Evidences For the Mechanisni Proposedsupporting
confidence: 82%
See 1 more Smart Citation
“…Several lines of evidence indicate that ATPases are implicated in active ion uptake (Hodges 1976, Stok et al 1981. In accordance with the mechanism proposed here, an ATPase reaction could be associated to each reaction leading from a P, form to the following Pj+, form of the carrier.…”
Section: Furtber Evidences For the Mechanisni Proposedsupporting
confidence: 82%
“…In fact experimental data are complex (Hodges 1976), but some of them appear relevant to us. Thus in oat roots, within some phases, a linear relation is found between Mg^' *' uptake and ATP hydrolysis by Mg^'^-stimulated ATPase (Stok et al 1981). Still more relevant in respect to our model is the finding in the same system (Stok et al 1981) that high Mg" concentrations sometimes inhibit ATPase.…”
Section: Furtber Evidences For the Mechanisni Proposedmentioning
confidence: 62%
“…Several studies show that all the Mg taken up by plants was initially physically adsorbed on the negative charges located at the root surface (Komaï, 1962;Stok et al, 1981;Kelly and Barber, 1991). Magnesium adsorption on root surfaces may therefore play a key role in the "heavy" isotope composition of plants.…”
Section: Root Level Processesmentioning
confidence: 97%
“…High levels of K and/or NH 4 -N decrease Mg and Ca uptake (Claassen and Wilcox, 1974) and K depresses the translocation of Mg and Ca from roots to shoots (Ohno and Grunes, 1985). Some studies on Mg and Ca uptake indicate that influx is passive, but that both elements are actively eftluxed (Macklon, 1975;Mack-Ion and Sim, 1976;Stok et al, 1981). Minotti et al (1969) treated intact wheat seedlings for 24 h with N0 3 -N salt solutions containing various cations as counterions plus CaS0 4 and found that Mg was the only cation eftluxed from the roots.…”
mentioning
confidence: 99%